Data interpolation using c2 rational quartic spline - Harim, A. (International Journal of Scientific and Technology Research, 2019)
This study discusses the construction of new C2 rational quartic spline scheme in from the quartic numerator and quadratic denominator with three parameters. Unlike the derivation of C2 continuity for some existing splines interpolation, the proposed rational quartic spline can achieve C2 continuity without the need to solve any system linear of equations. The main advantages of the proposed scheme is that we will obtain various C2 rational just by manipulating the free parameters. We test the proposed scheme to interpolate data and we compare the performance against established schemes in terms of root mean square error (RMSE) and coefficient of determination (R2). From numerical results, the proposed scheme is best than some existing schemes in terms of smaller RMSE and higher R2 value. Â© 2019, International Journal of Scientific and Technology Research. All rights reserved.